2012
DOI: 10.1176/appi.ajp.2011.11050711
|View full text |Cite
|
Sign up to set email alerts
|

Increased Medial Orbitofrontal and Amygdala Activation: Evidence for a Systems-Level Endophenotype of Bipolar I Disorder

Abstract: These results identify increased activity of the orbitofrontal cortex and the amygdala, related to heightened sensitivity to reward and deficient prediction error signal, as a candidate endophenotype of bipolar disorder. The results support a role of motivational processing in the risk architecture of bipolar disorder and identify a new systems-level therapeutic target for the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 34 publications
3
80
1
1
Order By: Relevance
“…During euthymia, Nusslock et al (2012) reported elevated ventral striatal and orbitofrontal activity during reward anticipation, but not outcome, in bipolar I patients, while Caseras et al (2013) found elevated ventral striatal activity in bipolar II patients rather than in bipolar I patients. A study by Linke et al (2012) using a probabilistic reversal learning task showed increased activity of the orbitofrontal cortex in response to reward and an attenuated prediction error signal in euthymic bipolar patients.…”
Section: Introductionmentioning
confidence: 99%
“…During euthymia, Nusslock et al (2012) reported elevated ventral striatal and orbitofrontal activity during reward anticipation, but not outcome, in bipolar I patients, while Caseras et al (2013) found elevated ventral striatal activity in bipolar II patients rather than in bipolar I patients. A study by Linke et al (2012) using a probabilistic reversal learning task showed increased activity of the orbitofrontal cortex in response to reward and an attenuated prediction error signal in euthymic bipolar patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, heightened reward sensitivity and reduced prediction error signal, as coded by the medial orbitofrontal cortex, was significantly correlated with the score of the behavioral activation system scale, lending further support to the behavioral system dysregulation model [2]. Last but not least, increased activity in the lateral orbitofrontal cortex, the dorsal anterior cingulate cortex, and the putamen in response to changing reward contingencies was also observed; it was suggested that this might represent a compensatory mechanism that aids in suppressing previously rewarded responses, thus allowing adequate performance during euthymia [104]. Interestingly, despite the significant negative correlation between amygdala response and psychotropic medication observed by Linke and coworkers (2012), no influence of psychotropic medication on brain responses upon delivery of reward or punishment have been observed in other studies [96,97,99,101].…”
Section: Delivery Of Positive and Negative Consequencesmentioning
confidence: 59%
“…Furthermore, decreased activation of the ventral prefrontal cortex and increased activation of the anterior cingulate cortex in response to the receipt of reward during a gambling task were reported for euthymic bipolar disorder patients [103]. In a recent study of our group, greater activation in response to reward and decreased deactivation in response to reversal of reward contingencies were observed in the medial orbitofrontal cortex in euthymic bipolar patients [104]. Further, activation of the amygdala in response to reversal of reward contingencies was increased.…”
Section: Delivery Of Positive and Negative Consequencesmentioning
confidence: 59%
See 2 more Smart Citations